Latex vascular occlusion balloons: histopathologic evaluation in a high-flow aortocaval fistula model. - Quisling, R G; Mickle, J P; Ballinger, W (American Journal of Neuroradiology, 1985)
The treatment of carotid-cavernous fistulae with intravascular, detachable latex balloons has become an accepted method. However, the histologic changes associated with such balloon embolization in a high-flow fistula state have not been described. This study evaluated the microscopic findings in a series of 12 rats studied over a 3-month period using an aortocaval fistula model. Small latex balloons were introduced into the venae cavae of rats in whom aortocaval fistulae had been surgically created 3 weeks earlier. The histopathologic changes associated with treatment of these fistulae were examined at 1, 2, 4, 6, 8, and 12 weeks. These changes can be characterized by an acute phase with thrombus formation and acute inflammation, followed by intermediate (or subacute) and chronic phases with diminishing inflammation and progressively increasing fibrosis of the fistula site. The latex balloon became encased by the fibrotic reaction but remained nonadherent and was easily removed at every study interval. No abscess formation or persistent vasculitis was apparent, and foreign-body giant cell reaction was minimal. Closure of the high-flow fistula site required the balloon to remain inflated for at least 7-9 days.